Spatial variability of soil physicochemical properties in a volcanic toposequence: implications for watershed management - Muh. Ansar; Muhammad Nathan (Jurnal Konseling dan Pendidikan, 2026)
The Jeneberang Watershed plays a vital role as a hydrological buffer in South Sulawesi but faces spatially varying land degradation pressures. This study aims to analyze the spatial variability of soil physical and chemical properties and their implications for hydrological functions along an elevation gradient (toposequence). A soil survey method was conducted using purposive sampling in three agroecological zones: Upstream (Malino, >1000 masl), Middle (Parangloe, 400-800 masl), and Downstream (Gowa/Samata, <100 masl) with a total of 15 representative pedons. Data were analyzed using ANOVA and Pearson correlation. Results showed significant polarization of soil characteristics (p<0.05). The upstream zone was dominated by sandy loam texture with high total porosity (62.4%), but constrained by acidic pH (4.2 – 4.8) and Aluminum toxicity (Exch-Al: 2.8 – 4.5cmol(+)/kg) due to intensive leaching. Conversely, the downstream zone showed high base accumulation (Base Saturation > 50%) with neutral pH, but had physical constraints in the form of high Bulk Density (1.35 g/cm3) and micropore dominance hindering infiltration. The study concludes that Jeneberang Watershed management requires site-specific approaches: the upstream zone needs organic matter amelioration to chelate Al and maintain structure, while the downstream zone requires soil aeration management to mitigate runoff.